METODOLOGI KUANTITATIF DALAM PENELITIAN KOMUNIKASI - Sutinah, Sutinah (Scriptura, 2007)
In many cases, qualitative and quantitative researches are different, although there are a lot of alikeness too, complementing to each other. All of social researchers have systematically collected and analyzed empirical data and carefully examined their patterns in order to understand and explain social life.Differences between qualitative and quantitative life can create confusion among students, researchers, and readers of research reports. Those who appraise qualitative research by means of quantitative research standards often get dissappointed, and such is the case with the contrary one. It is the best to appraise each of the styles. To appraise their respective strengths, it is very important to understand differences of researchers' orientation. One of differences between the two styles derives from the existing data characteristics. Soft data take form of impressions, words, sentences, photos, symbols, and so on, dictating research strategies and technique of data collection that is different compared to hard data, taking form of numbers. Another difference is that researchers qualitatively and quantitatively have varied assumptions on social life and different objectives. The difference can make tools used by other forces become unsuitable and irrelevant to others